Librarians’ Participation in the Systematic Reviews Published by Iranian Researchers and Its Impact on the Quality of Reporting Search Strategy - Eskrootchi, Rogheyeh; Shahraki Mohammadi, Azita; Panahi, Sirous; Zahedi, Razieh (Evidence Based Library and Information Practice)

(untitled) (University of Alberta Library, 2020)
Objective – The validity of the results from systematic review studies depends largely on the implementation and the reporting of the search strategy. Using an experienced librarian can greatly enhance the quality of results. Thus, the present study aimed to investigate the relationship between the librarian’s participation and the quality of reporting search strategy in systematic reviews published by Iranian researchers in medical fields.Methods – Three databases were searched to identify the systematic review studies conducted by Iranian researchers from 2008 to 2018. A total of 310 studies were selected using systematic random sampling, and the quality of their search strategy reports was reviewed by the Institute of Medicine checklist. A short questionnaire about the librarians’ participation in the search strategy of these studies was sent to the corresponding authors of the selected studies. A total of 229 questionnaires was returned. The data obtained from the questionnaire about the librarians’ participation in reporting search strategy in systematic review studies and also from the evaluation checklist for reporting search strategy in systematic review studies were analyzed by descriptive and inferential statistics.Results – The mean value of the evaluation checklist for reporting search strategy in systematic review studies was low. The librarians’ participation rate for these studies was 13.6%. No meaningful relationship was found between the librarians’ participation and the mean value of the evaluation checklist for reporting search strategy of systematic review studies. However, an investigation of the relationship between each of the items in the evaluation checklist for reporting search strategy in systematic review studies and librarians’ participation as the corresponding author or a member of the research team showed a meaningful relationship in five items.Conclusion – The results showed that the quality of reporting the search strategies in systematic reviews was low and the librarians’ participation in designing and reporting the search strategy in systematic reviews was limited. The authors of the systematic review studies, as well as the journals’ editors and referees, need to pay more careful attention to reporting the search strategy exactly and comprehensively. Employing librarians in this area can have a major impact on this part of systematic review studies.